Bulk plasmon polariton-gap soliton-induced transparency in one-dimensional Kerr-metamaterial superlattices - Cavalcanti, S. B.; Brandao, P. A.; Bruno-Alfonso, A. [UNESP]; Oliveira, L. E. (Optical Soc Amer, 2014)
We have performed a theoretical study of various arrangements of one-dimensional heterostructures composed by bilayers made of nondispersive (A)/dispersive linear (B) materials and illuminated by an obliquely incident electromagnetic wave, which are shown to exhibit a robust bulk-like plasmon-polariton gap for frequencies below the plasma frequency. The origin of this gap stems from the coupling between photonic and plasmonic modes that may be of a magnetic (electric) origin in a transversal electric (traversal magnetic) configuration yielding a plasmon-polariton mode. By substituting the nondispersive linear layer by a nonlinear Kerr layer, we have found that, for frequencies close to the edge of the plasmon-polariton gap, the transmission of a finite superlattice presents a multistable behavior and it switches from very low values to the maximum transparency at particular values of the incident power. At these frequencies, for those singular points where transmission becomes maximum, we find localized plasmon-polariton-gap solitons of various orders depending on the particular value of the incident power. Present results reveal, therefore, new gap plasmon-soliton solutions that are hybrid modes stemming from the resonant coupling between the incoming electromagnetic wave and the plasmonic modes of the dispersive material, leading to the transparency of a stack with nonlinear inclusions. (C) 2013 Optical Society of America